Pengaruh Literasi Keuangan Syariah dan Tingkat Pendidikan terhadap Minat Menggunakan Produk Tabungan BSI di Kota Jambi - Taufiq Ade Chandra; Maulana Yusuf; Aztyara Ismadharliani (JOURNAL OF SHARIA ECONOMICS, 2025)
This study aims to examine the effect of Islamic financial literacy and education level on the public's interest in using savings products at Bank Syariah Indonesia (BSI) in Jambi City. The study employed a quantitative approach using an explanatory research design. The population consisted of all residents of Jambi City, while the sample comprised 100 respondents, selected through purposive sampling. Primary data were collected using a structured questionnaire with a five-point Likert scale. The data were analyzed using multiple linear regression with the assistance of IBM SPSS Statistics version 27. Prior to hypothesis testing, the research instrument was tested for validity and reliability, followed by classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests.The results indicate that Islamic financial literacy has a positive and significant effect on the public's interest in using BSI savings products (t = 4.218; p < 0.05). Likewise, education level has a positive and significant effect on the interest in using BSI savings products (t = 5.525; p < 0.05). Simultaneously, Islamic financial literacy and education level significantly influence the public's interest in using BSI savings products (F = 114.949; p < 0.05). Furthermore, the coefficient of determination (Adjusted R²) of 0.697 indicates that 69.7% of the variation in the interest in using BSI savings products can be explained by Islamic financial literacy and education level, while the remaining 30.3% is influenced by other factors not included in this study.These findings suggest that improving Islamic financial literacy and educational attainment can enhance public interest in utilizing Islamic banking products. Therefore, Bank Syariah Indonesia is encouraged to strengthen financial literacy programs, expand public education initiatives, and collaborate with educational institutions and relevant stakeholders to promote greater awareness and utilization of Islamic banking services.